Evolution of Tropical Cyclone Properties Across the Development Cycle of the GISS‐E3 Global Climate Model. (5th January 2022) - Russotto, Rick D.; Strong, Jeffrey D. O.; Camargo, Suzana J.; Sobel, Adam; Elsaesser, Gregory S.; Kelley, Maxwell; Del Genio, Anthony; Moon, Yumin; Kim, Daehyun
Abstract: The next‐generation global climate model from the NASA Goddard Institute for Space Studies, GISS‐E3, contains many improvements to resolution and physics that allow for improved representation of tropical cyclones (TCs) in the model. This study examines the properties of TCs in two different versions of E3 at different points in its development cycle, run for 20 years at 0.5° resolution, and compares these TCs with observations, the previous generation GISS model, E2, and other climate models. E3 shares many TC biases common to global climate models, such as having too few tropical cyclones, but is much improved from E2. E3 produces strong enough TCs that observation‐based wind speed thresholds can now be used to detect and track them, and some storms now reach hurricane intensity; neither of these was true of E2. Model development between the first and second versions of E3 further increased the number and intensity of TCs and reduced TC count biases globally and in most regions. One‐year sensitivity tests to changes in various microphysical and dynamical tuning parameters are also examined. Increasing the entrainment rate for the more strongly entraining plume in the convection scheme increases the number of TCs (though also affecting other climate variables, and in some cases increasing biases). Variations in divergence damping did not have a strong effect on simulated TC properties, contrary to expectations based on previous studies. Overall, the improvements in E3 make it more credible for studies of TC activity and its relationship to climate. Plain Language Summary: Tropical cyclones, storms known as hurricanes, typhoons, or cyclones in different parts of the world, are one of the most dangerous natural hazards, and it is an important question whether they will get more powerful or common in our changing climate. Global climate models, used by scientists to study climate change, can simulate tropical cyclones, but in the models these storms tend to be weaker and less numerous than in the real world, and this is especially true for the previous generation climate model developed by NASA, known as GISS‐E2. We analyzed tropical cyclones in the newest version of this model, GISS‐E3, running at its highest resolution, in which the world is divided into grid boxes about 50 km wide. We found that the new version has more and stronger cyclones than the old version. While the storms are still weaker and less numerous than in the real world, GISS‐E3 now simulates storms strong enough that they would be called hurricanes instead of tropical storms, and it is comparable to its peer climate models in its representation of tropical cyclones. Key Points: The new NASA GISS‐E3 global climate model at 0.5° resolution simulates more realistic tropical cyclone activity versus the E2 version Hurricane intensity storms are now simulated, and the average storms are comparable to other 0.5° climate models Tropical cyclone counts in E3 are very sensitive to convective plume entrainment rates but not to divergence damping coefficients